Newsrooms in conflict : journalism and the democratization of Mexico - Hughes, Sallie (Pitt Latin American series., 2006)
"Newsrooms in Conflict examines the dramatic changes within Mexican society, politics, and journalism that transformed an authoritarian media institution into a hybrid system of journalism with significant implications for deepening democracy in the country. Using extensive interviews with journalists and content analysis spanning more than two decades, Sallie Hughes identifies the patterns of newsroom transformation that explain how Mexican journalism changed from a passive, and even collusive, monolithic institution into differential clusters of news organizations exhibiting citizen-oriented, market-driven, and adaptive authoritarian tendencies